Drivers of Government Activity in European Countries: Do Partisan Politics Still Divide East and West? - Joscha Beckmann; Rainer Schweickert; Markus Ahlborn; Inna Melnykovska (JCMS: Journal of Common Market Studies, 2020)
This article takes a novel look at the relationship between government activity, partisan preferences and varieties of capitalism. Evidence from panel regressions for 25 EU countries from 1990 to 2014 suggests that there are major divides among European countries in terms of the drivers of government activity, that is, government spending and government regulation. The European divide appears to be even more pronounced between liberal and coordinated economic systems than between the classical geographical divide of east and west, which is typically used in most contributions. While both divides apply to the determinants of government activity in general, a reversal of the classical partisan effect for the east is to be found only in specific cases and, is most likely in government spending in liberal eastern countries.
Keywords: 330; government activity; partisan preferences; varieties of capitalism